Expression of nuclear receptor corepressors and class I histone deacetylases in astrocytic gliomas - Campos, Benito; Lorenzo Bermejo, Justo; Han, Lin; Felsberg, Jörg; Ahmadi, Rezvan; Grabe, Niels; Reifenberger, Guido; Unterberg, Andreas; Herold-Mende, Christel (Cancer science, 2011)
Transcriptional repressors such as nuclear receptor corepressors (NCORs) and class I histone deacetylases (HDACs) are considered potential therapeutic targets in various human malignancies. In astrocytic gliomas, however, there is still a need to understand the role of these transcriptional repressors in tumor proliferation, tumor differentiation, and patient survival. We immunohistochemically analyzed the expression of NCOR1 and 2 as well as HDAC1, 2, and 3 on a tissue microarray comprising tumor samples from 283 astrocytic gliomas and correlated the expression levels with tumor differentiation, tumor proliferation, and patient survival. Strong nuclear expression was found in glioma cells for HDAC1, HDAC2, and NCOR2. In contrast, weak expression of NCOR1 and HDAC3 was detected in the cytoplasm and nuclei of tumor cells. HDAC3 expression was inversely associated with tumor grade. Consequently, increased HDAC3 expression was associated with better patient survival in univariate regression. Expression of HDAC1 and HDAC2 increased during tumor recurrence and malignant tumor progression, respectively, whereas expression of the remaining antigens did not seem to depend on tumor grade and was comparable to expression levels found in non-neoplastic brain tissues. Finally, we detected a positive association between HDAC2 expression and tumor proliferation as well as between NCOR1 and expression of the stem cell-associated intermediate filament protein nestin. Our findings suggest that “classical” transcriptional repressors are expressed in astrocytic tumors and that the roles of HDAC2 and HDAC3 in these tumors deserve further investigation.
Article first published online December 10, 2010
Gesehen am 27.06.2022